Analisis Implementasi Program Keluarga Harapan untuk Masyarakat Nelayan di Kecamatan Kragan Kabupaten Rembang Tahun 2016 - Ravanelly, Revan; Astrika, Lusia (Journal of Politic and Government Studies, 2018)
Family Hope Program (PKH) is a government policy to accelerate poverty alleviation for very poor families to access health and education services. The purpose of this research is to analyze the implementation of PKH and to know the factors that influence the implementation of PKH for fishermen community in Kragan Sub-district of Rembang Regency.The method used in this research is qualitative descriptive. The research was conducted at Department of Social, Women Empowerment and Family Planning of Rembang Regency, UPPKH of Rembang Regency and Kragan District with 12 persons including Head of Rehabilitation and Social Security of Department of Social, Women Empowerment and Family Planning of Rembang Regency; Coordinator of PKH Rembang Regency; Coordinator of PKH Kragan District; PKH Assistant of Kragan District; Education and Health Service Providers; and PKH participants who work as fishermen. Data collection techniques are carried out with interviews, documentation and literature studies.Based on the results of the research, PKH implementation in Rembang Regency with the theory of policy implementation according to George C. Edward III of the four implementation indicators, three of them have been implemented well and there is one indicator that has not run well that is the indicator of resources and also PKH not able to reduce the poverty rate in Rembang Regency because it was influenced by the low quality of very poor families and the abuse of PKH assistance by participants.The results of this study are expected to provide good benefits for the parties involved. Based on the results of this study, the authors propose a recommendation that is the empowerment of PKH participants to create independent business in order to be separated from the poverty chain, increasing the availability of infrastructure facilities needed PKH implementers and PKH participants to support the success of PKH and provide more understanding to PKH participants in the use of funds PKH assistance and awareness of those who are unable to receive PKH assistance.Keywords: Policy Implementation, Family Hope Program